Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1177/13524585231189641
|View full text |Cite
|
Sign up to set email alerts
|

High CD4+:CD8+ ratios with herpes zoster infections in patients with multiple sclerosis on dimethyl fumarate

Abstract: Background: Dimethyl fumarate (DMF) depletes CD8+ and CD4+ T cells, and cases of herpes zoster (HZ) in patients with multiple sclerosis (MS) on DMF have been documented. Objectives: To evaluate lymphocyte subsets in patients with MS who developed HZ on DMF (Tecfidera) compared to matched controls who did not develop HZ. Methods: We used linear mixed-effects models to test for differences in white blood cell count, lymphocyte percentage, absolute lymphocyte count, CD3+ percentage, absolute CD3+ count, CD4+ perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(24 reference statements)
0
0
0
Order By: Relevance
“…When the CD4/CD8 ratio is less than the turning point of 2, the risk of developing HZ in AIRD patients gradually increases as the CD4/CD8 ratio decreases. Another study has also demonstrated that changes in the CD4/CD8 ratio may elevate the risk of HZ occurrence in patients with MS, which was consistent with our study 28 . Therefore, changes in T-lymphocyte subsets should be detected during clinical workup and treatment; in particular, changes in the CD4/CD8 ratio should be emphasized.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…When the CD4/CD8 ratio is less than the turning point of 2, the risk of developing HZ in AIRD patients gradually increases as the CD4/CD8 ratio decreases. Another study has also demonstrated that changes in the CD4/CD8 ratio may elevate the risk of HZ occurrence in patients with MS, which was consistent with our study 28 . Therefore, changes in T-lymphocyte subsets should be detected during clinical workup and treatment; in particular, changes in the CD4/CD8 ratio should be emphasized.…”
Section: Discussionsupporting
confidence: 93%
“…An interesting study by Balshi et al 28 suggests that patients with multiple sclerosis (MS) who develop HZ while on dimethyl fumarate (DMF) have high CD4/CD8 ratio. MS is a chronic neurological disease that affects the central nervous system, and the efficacy of DMF in the treatment of MS has been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Another case demonstrated a significant decrease in CD8+ and CD4+ T lymphocytes in a patient receiving DMF, suggesting a potential link between DMF-induced lymphopenia and VZV reactivation with disseminated zoster [ 27 ]. Furthermore, a recent study found elevated CD4+/CD8+ ratios in patients with MS on DMF who developed HZ [ 28 ]. Additionally, a case of progressive multifocal leukoencephalopathy in DMF-treated patients without severe lymphopenia underscores the need for vigilance [ 29 ] as does the case of HSV encephalitis in a lymphopenic DMF-treated patient with MS, highlighting the potential implications of DMF-related lymphopenia for viral immunity [ 30 ].…”
Section: Discussionmentioning
confidence: 99%